Estimación del impacto económico del sector eólico en Galicia en el período 2000-2010 - Pedro Varela Vázquez; María del Carmen Sánchez Carreira; Xesús Pereira López (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
– Wind energy stands out among the main domestic renewable energy sources in Galicia. The economic impact quantification is crucial but there are several differential analysis of the temporal and permanent activities, among other factors. The main aim of this paper consists of the economic impact estimation of wind energy. The methodology is based on the input-output analysis, by means of the value chain examination and the productive structure updating, using a RAS variation. The results show a sector with additional output increase, both in temporal as well as permanent activities. Nevertheless, the paralysation of new wind farms restricts substantially the economic impact on the regional GDP.
Keywords: Q42; C67; 330; wind energy; economic impact; value chains; input-output; Galicia